RELATIONSHIP OF BLOOD SUGAR LEVELS WITH MORTALITY IN ACS PATIENT IN RSUD Dr. H. CHASAN BOESOIRIE - Putra, Muhammad Nuradin; Pratiwi, Dian; Anwar, Mawardy (Universitas Muhammadiyah Ponorogo, 2025)
Acute coronary syndrome is a disease process with a collection of symptoms caused by acute myocardial ischemia due to the presence of atherosclerotic plaques. It has become a health problem with the highest mortality rate in the world and high blood glucose levels are associated with poor clinical outcomes and increased risk of death in hospitalised patients. To determine the relationship between blood sugar levels and mortality in patients with acute coronary syndrome in RSUD Dr. H. Chasan Boesoirie in 2018-2023. This type of research is quantitative cross sectional analytical observational with a retrospective approach and using Spearman’s rho test. The sample totalled to 131 samples taken using medical record data with simple random sampling technique. Based on bivariate analysis, p-value = 0.003 (p0.05) with a correlation coefficient of 0.261 which means there is a relationship between increased blood sugar levels with mortality with a weak positive correlation. There is a relationship between blood sugar levels and mortality, namely the higher the blood sugar level, the higher the mortality